1990
DOI: 10.1051/apido:19900103
|View full text |Cite
|
Sign up to set email alerts
|

Diastatic activity in some unifloral honeys

Abstract: Summary — Determinations of diastatic activity in 12 groups of unifloral honey were made to study variability according to the botanical origin of the honey. Robinia, Citrus, Erica, Taraxacum and Arbutus honeys were found to have a very low enzyme content. On the contrary Hedysarum, Castanea, Honeydew, Eucalyptus and Thymus honeys showed high diastase activity. The relationship between the absorbance at 5 min and the diastatic index was quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
1
14
0
3
Order By: Relevance
“…In honey, HMF content is related to its quality and heat processing. Furthermore diastase activity has been related to the origin of the samples 36, 37. No sample exceeded the limits established for these variables.…”
Section: Resultsmentioning
confidence: 96%
“…In honey, HMF content is related to its quality and heat processing. Furthermore diastase activity has been related to the origin of the samples 36, 37. No sample exceeded the limits established for these variables.…”
Section: Resultsmentioning
confidence: 96%
“…The mean invertase content was 18.0 ± 5.8 IN. Persano‐Oddo et al. (1990), in a study of diastase activity in major Italian unifloral honey, reported low diastase activity in Arbutus honey, intermediate activity in Rhododendron and Helianthus honey, and higher activity in Hedysarum , Castanea and Eucalyptus honey.…”
Section: Resultsmentioning
confidence: 97%
“…The invertase, being more susceptible to damage by storage and heat, is used in some countries as an indicator for honey virginity and freshness; i.e., fresh and virgin honeys are supposed to have at least 10 Hardon invertase units or 64 international units, while honeys with low enzyme activity should have at least 4 units [21]. However, the diastase and invertase activities in honey vary in wide limits depending on botanical origin of honey [37,38] and thus, have a limited freshness indicating power; HMF is regarded as better quality criterion in this respect. [25,26] and for Acacia honey [39].…”
Section: Discussionmentioning
confidence: 99%